(untitled) (Journal of Creative Industry and Sustainable Culture, 2022)
All Mechanical Engineering students studying in Malaysian polytechnics have to take welding as a core subject. They will learn the basic theory in the classroom and proceed with instruction-based training in the workshop. With limited learning time in the classroom, students find it difficult to follow and understand everything that has been taught. Furthermore, welding is dangerous for beginners and the environment is hazardous to health. If students are not well prepared before going to the workshop, this might jeopardize themselves as well as the welding equipment. To help students be better prepared, a supplementary learning method is needed and the Mobile Arc Welding app has been introduced to them. A study has been conducted to determine whether the app contributes to the students’ learning process. The study was carried out among 67 mechanical engineering students of a polytechnic. The analysis involved Pearson Correlation and Regression in determining the impact of engagement, ease of use, learnability, satisfaction and usefulness on students’ motivation through the use of a welding app. The findings show that there are empirically positive and substantial correlations between motivation and engagement, satisfaction, and usefulness. However, there was no evidence of a positive and significant relationship between ease of use and learnability and welding learning motivation.